Kewenangan BKPM dalam Mencabut Izin Usaha Pertambangan - Hasti, Armin; Saleng, Abrar; Sumarji, Juajir (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The government's consideration in granting mining business permits is based on economic factors and state revenue and to maximize the utilization of mining potential to be processed and produced. The granting of mining business permits (IUP) by the Investment Coordinating Board (BKPM) provides benefits to the state and aims to present efficient and just mining management to the community. But in reality, as many as 1,118 mineral and coal mining company permits were revoked by BKPPM because they did not submit a work plan and budget (RKAB) and were not carried out. This research is a normative legal research by examining library materials or secondary data. This study uses a statutory approach, and a theoretical approach. Legally, IUP revocation has 3 (three) classifications, namely IUP revocation because the IUP holder does not carry out his obligations, commits a criminal act, and goes bankrupt. However, in reality many IUPs were revoked by the Head of BKPM because they were deemed not to comply with legal provisions, even though the authority possessed by the Head of BKPM did not yet have sufficient legal instruments to revoke the IUP because the basis of authority possessed by the Head of BKPM was only based on the Regulation of the Minister of Energy and Mineral Resources, even though legally based on the provisions of the law the delegation of authority received must be based on government regulations and or presidential regulations